Development of Solar Energy Lamp Using Arduino Uno - Ruddy Sanger; Viverdy Memah; Jocke Rapar; Moudy Kambey; Djamii Olii (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2022)
This study aims to design an electronic system from solar energy lamps using Arduino Uno and then implement it into a prototype circuit. This solar energy lighting system supports the green energy ecosystem in the implementation of solar cells in the design of cost-effective electronic systems. This automatic solar energy lamp system consists of solar panels and batteries as inputs, LDR and voltage sensors as references and sensors, Arduino Uno and relays as controllers, and LCD and LED lights as output circuits. The implementation results show that solar energy lamps using Arduino Uno can function properly. The solar energy stored in the battery can be used automatically as lighting at night without using electricity from PLN. It can automate the light in the room, eliminating the need to turn them off and on manually.